The curious world of Calpurnia Tate - Kelly, Jacqueline (Henry Holt and Company, 2015)
"In rural Texas in 1900, when a storm blows change into town in the form of a visiting veterinarian, twelve-year-old Callie discovers a life and a vocation she desperately wants. But with societal expectations as they are, she will need all her wits and courage to realize her dreams"--